Molecular and morphological characters of Helicotylenchus Steiner, 1945 species from Iran with a note on the identity of H. pseudorobustus (Steiner, 1914) Golden, 1956 - Divsalar, Nafiseh; Shokoohi, Ebrahim; Marais, Mariette; Mashela, Phatu W. (Zootaxa, 2020)
Helicotylenchus species were recovered from natural areas of three provinces (Mazandaran, Kerman and Guilan) in Iran, with morphological and molecular characteristics suggesting that they were Helicotylenchus minzi and Helicotylenchus pseudorobustus. A phylogenetic analysis of the two Helicotylenchus species using 28S rDNA placed H. pseudrobustus and H. minzi in a clade with 1.00 posterior probability. Results suggest that the Helicotylenchus population identified using molecular characteristics as H. pseudorobustus is a paraphyletic group, with hierarchical clustering analysis indicating a close relationship between the Iranian and the Chinese populations of H. pseudorobustus. In conclusion, further molecular studies within the genus Helicotylenchus are needed, especially for morphologically similar populations that have been recognized as separate species.